INVESTIGATION OF THE FLOW AROUND TWO TANDEM ROTATED SQUARE CYLINDERS USING THE LEAST SQUARE MOVING PARTICLE SEMI-IMPLICIT BASED ON VORTEX PARTICLE METHOD - Firdaus, Al-Faisal
Characteristics of the flow around two rotated square cylinders in tandem arrangements at low Reynolds numbers (Re) and normalized gap spacings (S) were numerically investigated using a newly proposed least square moving particle semi-implicit based on vortex particle method. The proposed method removes the background grid dependencies from the late vortex particle method and improves the computational cost using multiresolution particles. It is found that the proposed method captures the flow characteristics well. In this study, five vortex wake patterns are revealed at different Re (3 ? Re ? 150) and spacing (1.5 ? S ? 6.0). The time history and variations of aerodynamics coefficients, such as drag and lift coefficients, root mean square value of lift coefficient, and Strouhal number, alongside vorticity contours, are discussed to clarify each flow pattern’s characteristics. A significant increase in aerodynamics coefficients is observed for both cylinders at the critical spacing, which may range from 1.5 ? S < 3 depending on the Re. The Strouhal number has an increasing trend past the critical spacing at all selected Re. Meanwhile, the mean drag coefficient of both cylinders remains mostly the same. Conversely, the root mean square value of the lift coefficient of the downstream cylinder has a decreasing trend and, in specific cases, becomes lower than the upstream cylinder.